KEPRAKTISAN BUKU AJAR MIKROBIOLOGI UMUM : KAJIAN UJICOBA PENGEMBANGAN - Fitri Wijarini (Biopedagogia, 2021)
This study aimed to determine the practicality of general microbiology textbook. The research method used in RD, according to Borg and Gall. The data collection instrument was in the form of a questionnaire tested on a small-scale test and a large-scale test. The research subjects in the small-scale trial were 12 students, while in the large-scale trial, there were 40 students with high, medium, and low cognitive categories. The study results obtained a value of 85.33% in the very practical category for small-scale trials. In contrast, in large-scale trials, the value was obtained with a percentage of 85.66% with the very practical category. Keywords: practicality, microbiology, textbook.